2016
DOI: 10.18535/jmscr/v4i11.107
|View full text |Cite
|
Sign up to set email alerts
|

ECG Changes in Obese Individuals

Abstract: The electrocardiogram in 100 subjects was correlated with the severity of obesity. QRS vector shifted to the left with increasing obesity in 42%of people which indicates left ventricular hypertrophy. These changes were independent of age, sex and blood pressuire. Interventricular conduction defect was present in 21% of patients, but t wave inversion was in 14% only. 17% of people had normal ECG, whereas 3% of have showed sinus bradycardia & arrhythmia. The shift of QRS vector to the left and the conduction abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…In the previous studies, it was found that increase in LV wall thickness, LV mass and prevalence of echocardiographic LV hypertrophy are associated with obesity but not related to blood pressures (Karthikkeyan, Umadevi, and Gajapriya, 2016). It is agreed in this study according to the findings of systolic blood pressure, R wave and S waves.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the previous studies, it was found that increase in LV wall thickness, LV mass and prevalence of echocardiographic LV hypertrophy are associated with obesity but not related to blood pressures (Karthikkeyan, Umadevi, and Gajapriya, 2016). It is agreed in this study according to the findings of systolic blood pressure, R wave and S waves.…”
Section: Discussionsupporting
confidence: 86%
“…These hypervolemic and hyper dynamic status increases left ventricular work and lead to an increase in cardiac mass that is proportional to degree of obesity. Increased cardiac mass is due to increased muscle mass of left ventricle and not due to epicardial or myocardial fat infiltration (Karthikkeyan, Umadevi and Gajapriya, 2016).…”
Section: Introductionmentioning
confidence: 99%